Time Trends in the Incidence and Causes of Blindness in Israel - Skaat, Alon; Chetrit, Angela; Belkin, Michael; Kinori, Michael; Kalter-Leibovici, Ofra (American journal of ophthalmology, 2012)
To evaluate time trends in the incidence and causes of new cases of blindness in Israel between 1999 and 2008. Descriptive, retrospective population-based study. During the decade of the study, 19 862 inhabitants of Israel were newly registered as legally blind. Data were retrieved from the 1999 to 2008 annual reports of the National Registry of the Blind in Israel and were reviewed retrospectively. Specific rates by age, gender, calendar year, and cause of blindness were calculated. Total and cause-specific annual age-standardized rates were calculated as well. Findings were evaluated by the use of Poisson regression models. The age-standardized rate of incidence of newly registered legal blindness at the end of the studied decade was half of that at the beginning, declining from 33.8 per 100 000 in 1999 to 16.6 per 100 000 in 2008. The decline mainly was attributable to a decreased incidence of blindness resulting from age-related macular degeneration, glaucoma, diabetic retinopathy, and cataract. Contemporary interventions in ophthalmology combined with widely available universal free access to healthcare seem to be effective in causing a major reduction in the incidence of blindness.